Articular Chondroprogenitor Cells Maintain Chondrogenic Potential but Fail to Form a Functional Matrix When Implanted Into Muscles of SCID Mice. (October 2014) - Marcus, Paula; De Bari, Cosimo; Dell'Accio, Francesco; Archer, Charles W.
Objective . Articular cartilage is a complex tissue comprising phenotypically distinct zones. Research has identified the presence of a progenitor cell population in the surface zone of immature articular cartilage. The aim of the present study was to determine the in vivo plasticity of articular cartilage progenitor. Design . Chondropogenitor cells were isolated from bovine metacarpalphalangeal joints by differential adhesion to fibronectin. Cells were labeled with PKH26 and injected into the thigh muscle of severe-combined immunodeficient (SCID) mice. After 2 weeks, the muscles were dissected and cryosectioned. Sections were stained with safranin O and labeled for sox9 and collagen type II. Polymerase chain reaction analysis was carried out to determine plasticity for a number of tissue-specific markers. Full-depth chondrocytes acted as a control. Results . Fluorescent PKH26 labeled cells were detected after 2 weeks in all samples analyzed. A cartilage pellet was present after injection of freshly isolated chondrocytes. After injection with clonal and enriched populations of chondroprogenitors, no distinct pellet was detected, but diffuse cartilage nodules were found with regions of safranin O staining and Sox9. Low levels of collagen type II were also detected. Polymerase chain reaction analysis identified the presence of the endothelial cell marker PECAM-1 in one clonal cell line, demonstrating phenotypic plasticity into the phenotype of the surrounding host tissues. Conclusions . The bovine articular cartilage progenitor cells were able to survive in vivo postimplantation, but failed to create a robust cartilage pellet, despite expressing sox9 and type II collagen. This suggests the cells require further signals for chondrogenic differentiation.